Narrative, Knowledge and Moral Character in Art and Literature - David Thomas Carr (Ignatianum University Press, 2018)
Although the term 'narrative' has been subject to very loose usage, it should be clear that scientific theories cannot be considered as such in the same sense as literary and artistic works. But this clearly calls the latter into serious epistemic question. On the one hand, we are often drawn to saying that agents have learned or come to know (morally or otherwise) something from literary of other artistic fictions; on the other hand, their fictional status seems to preclude regarding this as knowledge. Drawing on insights from Plato's Socratic and other dialogues, this paper argues that such learning from art and literature should be deemed genuine knowledge of an epistemically uncontroversial kind.